Financial reporting practices of Singapore incorporated companies listed on the stock exchange - Andrew, Brian (Institutional Knowledge at Singapore Management University, 1989)
Our main objective for this survey is to gather information on the presentation of financial information and on the reporting practices by Singapore incorporated companies whose shares/stocks are quoted on the Stock Exchange of Singapore.